Care, justice et dépendance : introduction aux théories du care - Garrau, Marie; Goff, Alice Le (Presses Universitaires de France, 2010)
Ce livre retrace le parcours théorique de la notion de dépendance dans la philosophie féministe contemporaine, de la critique du fonctionnement du concept dans la rhétorique de l’État libéral aux modalités de son inclusion dans une théorie de la justice. Deux axes se dégagent, qui convergent dans une tentative de redéfinition de la notion d’autonomie : les relations de dépendance constituent le point de départ de l’éthique du « care » ou de la sollicitude, qu’il s’agira de présenter ici ; elles ont en outre suscité des reformulations importantes des théories de la justice sur la base d’une anthropologie politique qui cherche à prendre acte de la constitution relationnelle des agents moraux. L’enjeu de ces réflexions n’est donc pas simplement de réévaluer la notion de dépendance, mais aussi de fournir un fondement normatif à l’inclusion des personnes dépendantes dans la communauté morale et politique, voire d’élaborer une conception renouvelée de la citoyenneté.
Keywords: approches et analyses; autonomie; capitalisme; care; discipline; justice sociale; philosophie; politiques néolibérales; projet charge mentale; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; théorie du care

Geography and gender: Feminism and a feeling of justice - Wright, Melissa W. (Progress in Human Geography, 2010)
The recent emphasis on emotional geographies has turned critical attention to the connections linking affect and social justice. It is hard to imagine this ‘emotional turn’ in the field without much of the ground having been laid by feminist challenges to epistemology, objectivity, rationality, to the gendering of knowledge and the conceptualization of human embodiment, psychic life, subjectivity, and political agency, all in relation to power so often substantiated around a belief that the public and the private are discrete and oppositional domains necessary for organizing social, economic, and political life. In this report, I address the following questions. How can feminist and emotional geography tighten their connections, fuel their shared passions and generate a synergy of scholarship oriented toward activism and progressive change? How can geographies of feeling broaden the path for justice that feminism endeavors to plow? In doing so, I continue my emphasis on research that grounds theoretical discussion with research conducted in activist projects conducted in the name of social justice. I do so as a matter of my own emotional investments – I firmly believe that scholarship must engage with the ways in which people beyond the academy wrestle with the concepts in their daily lives that scholars contemplate, sharpen, and circulate through academic production. So the debates that we scholars so often have with ourselves over the finer points of theory reveal, in my view, their greater significance when they provide tools useful for people who seek to create kinder and more compassionate worlds. Thus, I highlight the scholarship that creates toolkits out of feminist scholarship, emotional geographies, and research on social justice.
Keywords: approches et analyses; care; discipline; genre; géographie; justice sociale; militance; ressource en ligne; sciences humaines; thématiques; travail; travail du care; émotions